Biased hate crime perceptions can reveal supremacist sympathies - Leander, N. Pontus (Proc Natl Acad Sci U S A, 2020)
People may be sympathetic to violent extremism when it serves their own interests. Such support may manifest itself via biased recognition of hate crimes. Psychological surveys were conducted in the wakes of mass shootings in the United States, New Zealand, and the Netherlands (total n = 2,332), to test whether factors that typically predict endorsement of violent extremism also predict biased hate crime perceptions. Path analyses indicated a consistent pattern of motivated judgment: hate crime perceptions were directly biased by prejudicial attitudes and indirectly biased by an aggrieved sense of disempowerment and White/Christian nationalism. After the shooting at a synagogue in Pittsburgh, Pennsylvania, disempowerment-fueled anti-Semitism predicted lower perceptions that the gunman was motivated by hatred and prejudice (study 1). After the shootings that occurred at two mosques in Christchurch, New Zealand, disempowerment-fueled Islamoprejudice similarly predicted lower hate crime perceptions (study 2a). Conversely, after the tram shooting in Utrecht, Netherlands (which was perpetrated by a Turkish-born immigrant), disempowerment-fueled Islamoprejudice predicted higher hate crime perceptions (study 2b). Finally, after the Walmart shooting in El Paso, Texas, hate crime perceptions were specifically biased by an ethnonationalist view of Hispanic immigrants as a symbolic (rather than realistic) threat to America; that is, disempowered individuals deemphasized likely hate crimes due to symbolic concerns about cultural supremacy rather than material concerns about jobs or crime (study 3). Altogether, biased hate crime perceptions can be purposive and reveal supremacist sympathies.